Racial Resentment and the Death Penalty. (27th March 2023) - Baumgartner, Frank R.; Caron, Christian; Duxbury, Scott
Abstract: We explore the annual number of death sentences imposed on black and white offenders within each US state from 1989 through 2017, with particular attention to the impact of aggregate levels of racial resentment. Controlling for general ideological conservatism, homicides, population size, violent crime, institutional and partisan factors, and the inertial nature of death sentencing behavior, we find that racial hostility translates directly into more death sentences, particularly for black offenders. Racial resentment itself reflects each state's history of racial strife; we show powerful indirect effects of a history of lynching and of racial population shares. These effects are mediated through contemporaneous levels of racial resentment. Our findings raise serious questions about the appropriateness of the ultimate punishment, as they show its deep historical and contemporary connection to white racial hostility toward blacks.